2006
DOI: 10.1097/01.gim.0000250204.97620.36
|View full text |Cite
|
Sign up to set email alerts
|

Genetic services for men: The preferences of men with a family history of prostate cancer

Abstract: Purpose: Men have a lower uptake of genetic services than women; however, the specific needs and preferences of men at risk of genetic conditions other than hereditary breast ovarian cancer are not known. We ascertain the information preferences of men with a family history of prostate cancer. Methods: Unaffected men and their partners were administered a written questionnaire. Results: Responses were received from 280 men (response rate: 59.2%) and 174 partners (response rate: 74%). Most men (59.6%) reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
(46 reference statements)
1
18
1
Order By: Relevance
“…It may be anticipated that families who are enrolled on the kConFab database have a higher level of awareness of their genetic risk and access to genetic information that may not be readily available to the broader high-risk community. These findings are in contrast to those of Gaff et al, 37 where 34% of men with a family history of prostate cancer reported that they only wanted to receive good information. However, we framed our question differently asking whether men wanted to receive all information good or bad, whereas Gaff et al asked whether men wished to receive good or bad information.…”
Section: Men's Information and Decision-making Preferencescontrasting
confidence: 99%
See 1 more Smart Citation
“…It may be anticipated that families who are enrolled on the kConFab database have a higher level of awareness of their genetic risk and access to genetic information that may not be readily available to the broader high-risk community. These findings are in contrast to those of Gaff et al, 37 where 34% of men with a family history of prostate cancer reported that they only wanted to receive good information. However, we framed our question differently asking whether men wanted to receive all information good or bad, whereas Gaff et al asked whether men wished to receive good or bad information.…”
Section: Men's Information and Decision-making Preferencescontrasting
confidence: 99%
“…These results are similar to those reported in our previous study of the expectations of women from high-risk breast cancer, 28 to other studies in women from high-risk breast cancer families, 38,39 and two studies of men at high risk for prostate cancer. 37,40 In line with our hypotheses, higher levels of cancer-related anxiety (intrusion and avoidance) predicted a higher value placed by men on receiving both information and emotional support. However, it should be noted that the cancer-related anxiety levels in these men were not high, with less than a dozen men scoring above the clinically significant cut-off.…”
Section: What Men Valued From the Familial Cancer Clinicsupporting
confidence: 73%
“…As reported previously, 25,26 a total of 504 questionnaires were mailed out; 23 packages were returned to sender, and eight men were found to be deceased. Of the remaining 473 eligible participants, 59% (51% in the family study and 73% in the self-selected sample) returned completed questionnaires.…”
Section: Response and Respondent Characteristicsmentioning
confidence: 86%
“…However, should such services be established, it is important to have some insight into the beliefs men might hold about their options before attending a service 37 and actions they may have already undertaken to reduce their risk. We have previously reported that the greatest need of men with a family history of prostate cancer was to obtain information about risk management 25 and that most are managing their risk by undergoing surveillance. 26 In this study, we extend these data by considering other modifications men have made to their health behavior, finding that 39% reported having made changes in response to their family history alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation